2019
DOI: 10.24313/jpbl.2019.00171
|View full text |Cite
|
Sign up to set email alerts
|

Priority Analysis of PBL Evaluation Score using AHP

Abstract: http://creativecommons.org/licenses/ by-nc/4.0/) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. www.ejpbl.org 54Purpose: The aim of this study was to improve the objectivity of an assessment scale by applying the Analytic Hierarchy Process (AHP) methodology with the learners themselves determining the weightings against the importance of evaluation factors. Methods: By analyzing assessment results of 20 respondents, cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…[14][15][16] But literature revealed that there is no empirical evidence that problem-based learning improves knowledge base and clinical problem-solving skills so resources required for conducting it cannot be justified. [17][18][19] As it is a new teaching strategy, students have limited knowledge about how it is conducted and its process. Problem-based learning has a group of resilient followers and a group of tough pessimists, too, but most of the medical educationists agree that hybrid curriculum is the best option which includes both traditional lecture-based learning as well as problem-based learning.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] But literature revealed that there is no empirical evidence that problem-based learning improves knowledge base and clinical problem-solving skills so resources required for conducting it cannot be justified. [17][18][19] As it is a new teaching strategy, students have limited knowledge about how it is conducted and its process. Problem-based learning has a group of resilient followers and a group of tough pessimists, too, but most of the medical educationists agree that hybrid curriculum is the best option which includes both traditional lecture-based learning as well as problem-based learning.…”
Section: Discussionmentioning
confidence: 99%